Linguistic and stylistic analysis of the creative revisions of E. Charents' poem "The Danthe Legend" - Nersisyan, Narine (History and Culture, 2026)
A comparative analysis of a writer's creative revisions offers a new opportunity to uncover his linguistic and stylistic observations, the development of aesthetic principles and the process of refining style. The aim of this article is to present the full spectrum of changes in the young Charents' stylistic thinking, based on the creative history of the poem "The Danthe Legend". The study is based on the printed texts of the poem from 1916, 1922 and 1932․ Additionally, the final corrections made by Charents in his handwriting on the 1932 printed text, which were not included in the academic publication, are being published and comprehensively analyzed for the first time.
Keywords: Comparative analysis of versions; Artistic precision; Creative adaptation; Emphasis on the psychological aspect of speech; Epithet; Intensification of metaphor; Manuscript; Original